EthReview: An Ethereum-based Product Review System for Mitigating Rating Frauds. Issue 100 (January 2021) - Zulfiqar, Maryam; Tariq, Filza; Janjua, Muhammad Umar; Mian, Adnan Noor; Qayyum, Adnan; Qadir, Junaid; Sher, Falak; Hassan, Muhammad
Abstract: On an e-commerce platform, a buyer's decision about the purchase of products is highly dependent on the existing reviews of that product. These reviews provide a judgment metric about the quality of the products and the credibility of the sellers. Popular e-commerce platforms (like eBay, Amazon, etc.) receive and store a lot of customer reviews regularly. However, these e-commerce platforms are prone to various kinds of rating frauds (intended towards bad-mouthing and ballot-stuffing) carried by the fake buyers and fraudulent sellers to promote or demote certain products. Moreover, these e-commerce platforms are under the control of a single authority and are prone to tampering of the reviews by the centralized authority itself to increase product sales. These fake and tampered reviews lead towards bad online buying experience and a lack of trust in e-commerce platforms. In this paper, we propose a decentralized Ethereum based product review system, EthReview, which maintains the integrity of product reviews and is resilient against rating frauds. Our solution proposes a consortium network of randomized peer-to-peer (P2P) endorser nodes for the validation and verification of the truthfulness of product reviews. The honest reviewers are given incentives in the form of discount tokens for encouraging honest behavior in the system while the fraudulent behavior is penalized. We also provide security and performance analysis of EthReview to evaluate its robustness and resilience against different forms of rating fraud.